Pelatihan Kewirausahaan untuk Peningkatan Ketahanan Ekonomi di Masyarakat Malino - Arniati, Arniati; Rustam, Andi; Asdi , Asdi; Andrisa , Andrisa; Adiningrat, Andi Arifwangsa (Jurnal SOLMA, 2025)
Background: Introduction, Malino, as a rural community that relies on natural resources, faces various economic challenges. The aim of this activity is to improve the entrepreneurial skills of the Malino community in order to strengthen economic resilience based on productive businesses. Method: Methods names of Malino community partners, with 12 participants, survey method, outreach and training. Data collection through participatory observation, interviews, and evaluation of business results. Result: The results of the service show that the community is very enthusiastic and actively participates in the activities carried out, and there is a strong desire in the community to open a business or become an entrepreneur. Conclusion: Increased skills and understanding in entrepreneurship.